The impact of duration of residence on cause-specific mortality: a cohort study of migrants from the Former Soviet Union residing in Israel and Germany - Ott, Jördis Jennifer; Paltiel, A. M.; Winkler, Volker; Becher, Heiko (Health & place, 2010)
A cohort study of migrants from the Former Soviet Union in Israel (N=528,848) and in Germany (N=34,393) was conducted. The impact of length of residence on cause-specific mortality was investigated using Poisson regression and differences between the migrant groups were assessed. In both migrant cohorts, all cause mortality in males but not in females significantly decreased with increasing duration of residence (RR=0.76, 95% CI: 0.73-0.79 for 9+years of residence compared to 0-3 years), specifically in Israel for infectious diseases, cancer and CVD. For male and female migrants in Israel there was a large reduction in external cause mortality. The cancer risk in male migrants declined from 1 to 0.76 (95% CI: 0.69-0.83) and in female migrants to 0.85 (95% CI: 0.78-0.93) after nine and more years of stay. Adjusting for several covariables, there were differences between migrants in the cause of death patterns in the two host countries, which may be associated with differences in their initial conditions or with effects of the destination country. The study highlights the need for migrant-specific prevention approaches.